2020
DOI: 10.1016/j.dcn.2020.100819
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic and non-linguistic non-adjacent dependency learning in early development

Abstract: Highlights Non-adjacent dependency learning shows a developmental shift during the third year of life. 2-year-old children can learn non-adjacent dependencies in linguistic material from passive listening, while 3-year-old children cannot. Non-adjacent dependency learning in 2-year-olds is subserved by left-hemisphere temporal, inferior frontal and parietal brain regions. The developmental trajectory for non-adjacent dependency learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 60 publications
3
35
3
Order By: Relevance
“…Similarly, it is possible that different measures, such as the head-turn preference procedure compared to ERPs and different NAD learning paradigms, tap into different learning processes. This difference in measures might also explain the differences between our study and a recent study using a similar paradigm with fNIRS, in which we found NAD learning from the same Italian sentences in 2-year-old, but not 3-year-old children (van der Kant et al, 2020). While fNIRS informs us about the brain areas underlying NAD learning during early childhood, EEG may be more sensitive to detect children’s decreased response to NAD violations at 3 years of age.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Similarly, it is possible that different measures, such as the head-turn preference procedure compared to ERPs and different NAD learning paradigms, tap into different learning processes. This difference in measures might also explain the differences between our study and a recent study using a similar paradigm with fNIRS, in which we found NAD learning from the same Italian sentences in 2-year-old, but not 3-year-old children (van der Kant et al, 2020). While fNIRS informs us about the brain areas underlying NAD learning during early childhood, EEG may be more sensitive to detect children’s decreased response to NAD violations at 3 years of age.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, in young children, syntactic information triggers activation in the left temporal cortex, but not the left inferior frontal cortex; at 3 years of age, at the latest, both regions are activated during syntactic processing (Dehaene-Lambertz et al, 2002. In summary of these results, (Friederici et al, 2011;Mueller et al, 2019;van der Kant et al, 2020) compared to older children and adults (Friederici et al, 2013;Mueller et al, 2012;Mueller et al, 2019). This advantage would decrease gradually with age, as indicated by the linear decrease in our study.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations